2019
DOI: 10.1016/j.ijrobp.2019.06.493
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of NRG Oncology/RTOG 0321 A Phase II Trial of Combined High Dose Rate Brachytherapy and External Beam Radiotherapy for Adenocarcinoma of the Prostate

Abstract: , biochemical failure was not associated with clinical stage, risk group, Gleason or baseline PSA. Distant metastases-free survival was 98% at 5 years. Conclusion: Despite linear quadratic considerations, single fraction 19 Gy is inferior to two fractions of 13.5 Gy, which appears to be highly effective. Single fraction 19 Gy is associated with an unacceptable rate of local failure. As recurrence is predominantly at the site of initial bulk disease, further dose escalation either focally to the dominant nodule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…No grade 3 or higher acute or late toxicities were observed in the current study. The low toxicity is favorable when compared to RTOG 0321, which utilized HDR brachytherapy boost conventionally fractionated external beam radiation, and prior studies of HDR brachytherapy boost with hypofractionated EBRT to the prostate and seminal vesicles without pelvic radiation [ 22 ]. Shahid et al and Tharmalingam et al have both reported very low rates of grade 3 or higher GI and GU toxicities in of 125 and 411 patients treated with a 15 Gy single fraction HDR boost with 37.5 Gy in 2.5 Gy per fraction of EBRT to the prostate and seminal vesicles after roughly 5 years of follow-up [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…No grade 3 or higher acute or late toxicities were observed in the current study. The low toxicity is favorable when compared to RTOG 0321, which utilized HDR brachytherapy boost conventionally fractionated external beam radiation, and prior studies of HDR brachytherapy boost with hypofractionated EBRT to the prostate and seminal vesicles without pelvic radiation [ 22 ]. Shahid et al and Tharmalingam et al have both reported very low rates of grade 3 or higher GI and GU toxicities in of 125 and 411 patients treated with a 15 Gy single fraction HDR boost with 37.5 Gy in 2.5 Gy per fraction of EBRT to the prostate and seminal vesicles after roughly 5 years of follow-up [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…High-dose rate (HDR) prostate brachytherapy is a standard-of -care treatment option for favorable risk, 1 unfavorable risk, 2,3 and radiorecurrent 4,5 prostate cancer. HDR brachytherapy involves the insertion of hollow needles into the prostate gland under transrectal ultrasound (TRUS) guidance.…”
Section: Introductionmentioning
confidence: 99%